Efektivitas Kebijakan Pemerintah Tentang Pengembangan Kompetensi Kerja Melalui Program Kartu Prakerja Studi Program Kartu Prakerja Dalam Mengatasi Pengangguran Di Kabupaten Tebo Provinsi Jambi - Doni Rahman; Khairul Rahman (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2021)
The Government's Policy on the Development of Work Competencies through the Pre-Employment Card ProgramThe Pre-Employment Card Program in Overcoming Unemployment in Tebo Regency, Jambi Province is implemented bythe Implementing Management of the Pre-Employment Card Program and assisted by the Tebo Regency Department ofIndustry, Trade and Manpower. This program is structured to develop work competencies, increase productivity andcompetitiveness of the workforce, and develop entrepreneurship, the main objective is to provide training to the workforce so that the workforce can work. Therefore, the training in the program must be in accordance with the needs of the existing labor market. The purpose of this study was to determine the effectiveness of the pre-employment card program in overcoming unemployment in Tebo Regency, as well as to determine the factors that influence the implementation of the pre- employment card program in Tebo Regency. The method used is qualitative using primary and secondary data. The results of the study on the effectiveness of the Government's Policy on the Development of Work Competenciesthrough the Study Pre-Employment Card Program The Pre-Employment Card Program in Overcoming Unemployment in Tebo Regency, Jambi Province is indeed still Less Effectiv because the pre-employment card program has not yetconfirmed employment after participants become alumni of the pre-employment card. However, in terms of the accuracy of program targets, program socialization and program monitoring can be said to be effective.